Proline Based Organocatalysis: Supported and Unsupported Approach - Upadhyay, Praveenkumar; Srivastava, Vivek (Current Organocatalysis, 2016)
Background: This review article, mainly focuses on the proline-based supported and unsupported organocatalysis. Organocatalysis, where low molecular weight organic molecules such as α- amino acids, α-hydroxy acids, nucleic acids and carbohydrates are used as catalysts (in stoichiometric amounts) to catalyze various organic transformations such as Aldol, Mannich and Michael reactions in a rapidly expanding segment of organic synthesis. Easy operational process, easy availability of the catalysts, selectivity, productivity and low price make such organocatalyzed organic transformations an attractive alternative to metal-mediated reactions. Methods: Although organocatalysts have many striking features, but this catalytic system also suffers from poor solubility in conventional solvent systems, high catalyst loading and catalyst recycling. Recently ionic liquids, PEG, montmorillonite clays silica and cyclodextrine were identified as good supports to overcome partly these boundaries. The supported systems offer often good compromises in terms of selective product with the added benefits of catalysts recyclability. Results: In this review, heterogenized organocatalysts will be discussed in detail, which are immobilized/ supported on organic as well as inorganic supports to effectively catalyze chiral organic transformations of topical interests. We also compared various supported and non-supported aminocatalysts, particularly focusing on the C-C bond forming reactions. The review offers critical views on the future scope, research advices, and academic as well as industrial benefits out of proline-based supported organocatalysis. Conclusion: Immobilization of organocatalysts may provide answers at least partly to the at tents. They may allow low catalyst loading improved selectivity, recyclability and easy separation of the catalyst. The often observed lower catalyst activity and the required multistep preparation are often mentioned difficulties. The examples covered in review article have explained the significant application of supported and unsupported strategies on asymmetric organocatalysis, to improve easy handling and good applicability in a number of useful examples. In some of them, a surprising, enhanced efficiency and selectivity were achieved on the basis of the proper choice of immobilization protocol and type of supports type. Surprisingly, in most of the cases the supported proline catalyst was recovered and recycled for the limited number times still suffers with limited substrate scope. We can say no covalent immobilization represents one of the feasible methods to be further reconnoitered. Further studies will certainly improve the availability of these systems, in particular, for industrial applications.
Keywords: supported organocatalysis